SAT0632-HPR The Efficacy of Biologics on Health Status Including Psychological Status, Self-Efficacy and Patient Satisfaction in Patients with Rheumatoid Arthritis. (15th July 2016) - Fusama, M.; Yukioka, K.; Kuroiwa, T.; Yukioka, C.; Inoue, M.; Higashi, K.; Ogata, A.; Murata, N.; Kuritani, T.; Maeda, K.; Sano, H.; Yukioka, M.; et al.
Abstract : Background: Biologics are effective for improving disease activity in patients with rheumatoid arthritis (RA). We also reported the efficacy of biologicals on health status [1]. However, efficacy of biologics on psychological status, self-efficacy and patient satisfaction in RA patients is not well evaluated. Objectives: We evaluated improvement of health status, psychological status, self-efficacy and patient satisfaction in patients with RA treated with biologics. Methods: The patients with RA who were planning to be treated with the biologics (adalimumab (ADA), tocilizumab (TCZ) and abatacept (ABT)) were enrolled. Disease activity was evaluated using SJC, TJC, PGA and CDAI. Psychological status was examined using the Hospital Anxiety and Depression Scale-Depression (HADS-D) and Anxiety (HADS-A). Self-efficacy and health status including patient satisfaction were assessed using the General Self-Efficacy Scale (GSES) and the Arthritis Impact Measurement Scale 2 (AIMS-2), respectively. Comparison analysis was performed between the baseline and 24 weeks after biological therapy. To further investigate the items related to satisfaction, correlation analysis was performed between patient satisfaction and disease activity and health status including psychological status. Data analyses were performed utilizing Wilcoxon rank-sum test and Spearman correlation analysis. Results: Twenty-six patients (male/female: 7/19) (ADA: 8, TCZ: 9, ABT: 9) were evaluated. Patients' characteristics were as follows: median (interquartile range) age of 57 (49.2 - 75.0) years and duration of 2.9 (0.8 - 5.5) years. SJC, TJC, PGA and CDAI showed statistically significant improvement at week 24 compared to the baseline (p<0.0001, for each of all items). In the components of AIMS-2, "physical", "symptom", "affect" and "role" improved significantly at week 24 compared to the baseline, while "social interaction" did not improve. Patient satisfaction and GSES also improved significantly at week 24 (p<0.0001, p=0.0124, respectively). As for psychological status, HADS-A and HADS-D improved significantly at week 24 compared to the baseline (p=0.018, p=0.0143, respectively). Patient satisfaction showed statistically significant correlation with SJC (r=0.686, p<0.0001), TJC (r=0.758, p<0.0001), PGA (r=0.586, p<0.0001), HADS-A (r=0.561, p<0.0001) and HADS-D (r=0.512, p=0.0001). PGA and TJC were also correlated with HADS-A (r=0.374, p=0.0062, r=0.325, p=0.018, respectively) and HADS-D (r=0.412, p=0.0024, r=0.392, p=0.0040, respectively). Moreover, patient satisfaction was also statistically significantly correlated with "physical" (r=0.804, p<0.0001), "symptom" (r=0.751, p<0.0001), "affect" (r=0.746, p<0.0001) and "role" (r=0.717, p<0.0001), "social interaction" (r=0.279, p=0.0476) of AIMS-2. Conclusions: Biologics were effective in improving psychological status, patient satisfaction and self-efficacy as well as disease activity and health status. For further improving patient satisfaction, psychological support and social assistance by health professionals' team in addition to appropriate treatment may be required. References: Fusama M, et al. Mod Rheumatol 2013; 23: 276–83. Disclosure of Interest: None declared